2019
DOI: 10.31703/gssr.2019(iv-i).08
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Exploration of the Effect of Differentiated Teaching Method vs. Traditional Teaching Method on Students’ Learning at ‘A’ level

Abstract: This study explores the effect of differentiated teaching method vs. traditional teaching method on students’ learning at ‘A’ level. It is an experimental research, conducted in Aitchison College. By applying simple random sampling technique, 70 students are selected as a sample from the population. Pre-test and post-test are conducted for data collection. Research investigates, how differentiated method of teaching effects learners’ academic achievement. The retention level of the students who are taught via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Hal ini terlihat pada adanya peningkatan rata-rata hasil belajar peserta didik setelah melakukan pembelajaran secara berdiferensiasi seperti ditunjukkan pada Gambar 3. Pembelajaran berdiferensiasi memberikan pengalaman belajar peserta didik yang sesuai dengan karakteristik individu, sehingga mendukung proses belajar yang lebih baik bagi setiap individu peserta didik (Dalila et al 2022;Kamran, Munir, and Wattoo 2019). Selain itu, pembentukan kelompok belajar sesuai dengan karakteristik gaya belajar yang sama dapat memberikan iklim belajar yang saling mendukung dan saling berkolaborasi untuk ketercapaian tujuan pembelajaran (Andini et al 2016).…”
Section: Siklus IIunclassified
“…Hal ini terlihat pada adanya peningkatan rata-rata hasil belajar peserta didik setelah melakukan pembelajaran secara berdiferensiasi seperti ditunjukkan pada Gambar 3. Pembelajaran berdiferensiasi memberikan pengalaman belajar peserta didik yang sesuai dengan karakteristik individu, sehingga mendukung proses belajar yang lebih baik bagi setiap individu peserta didik (Dalila et al 2022;Kamran, Munir, and Wattoo 2019). Selain itu, pembentukan kelompok belajar sesuai dengan karakteristik gaya belajar yang sama dapat memberikan iklim belajar yang saling mendukung dan saling berkolaborasi untuk ketercapaian tujuan pembelajaran (Andini et al 2016).…”
Section: Siklus IIunclassified
“…The students' inadequate 3D and spatial capability limits the effectiveness of conventional teaching materials, whereas the student's existing spatial capacity also restricts the instructional effectiveness. Spatial visualisation abilities should not be underestimated and ignored in the learning process as these abilities are related to student achievement and in-depth topic understanding (Kamran et al, 2019;Yao et al, 2019). Furthermore, utilising an actual 3D model representation resulted in better learning outcomes than utilising traditional three-view diagrams (Huang and Lin, 2016).…”
Section: Challenge 5: Lack Of Emphasis On Spatial Visualisation Capabilities In Educationmentioning
confidence: 99%
“…Shahzadi (2019) in her study showed that deductive method of teaching was more effective for overcrowded class in public schools. The students learn more and give better result in subjects as compared to traditional teaching method (Kamran, Munir & Wattoo, 2019). Taking into account the fact that "teaching is more important than knowledge", the study is designed to know the effectiveness of accelerated learning to facilitate the application of concepts of English language at secondary level.…”
Section: Global Social Sciences Review (Gssr)mentioning
confidence: 99%